Teaching modules: Levels of cross-subsidising at a South African university - Serfontein, C.; Smit, A. v. A. (South African Journal of Higher Education, 2021)
Traditional universities, typically presenting face-to-face education on-campus, are facing their biggest survival crisis in decades. COVID-19 fast-tracked the impact of the Fourth Industrial Revolution (4IR) on universities in terms of online education, rethinking their core disciplines and even their role in society. In a matter of months, most universities had to embrace technology to educate their students. Huge amounts of money had to be spent to retrain staff and invest in technology, leading to significant increases in spending. In addition, the world is experiencing a massive rise in unemployment, which is already leading to declining student numbers and a need for more affordable education. The primary research objective of this article was to determine the levels of cross-subsidy of teaching modules at a South African university using cost and management accounting principles. The sample consisted of 3 689 modules with 286 831 students enrolled during 2018 at a selected South African university. The authors of this article are convinced that the costing methodology applied in this study is unique and sound, and, in spite of the fact that the results reflect the figures of only one university, it is quite likely that most traditional universities are facing the same dilemma. The results of this study indicated that 49,7 per cent (1 769) of the teaching modules at the related university did not cover their direct cost in 2018. In addition, the 1 769 modules not covering their direct costs, accounted for only 5,2 per cent of all enrolments. Hence, if the selected university had to close 47,9 per cent of the modules not covering their direct costs, it would only impact 14 867 of 286 832 enrolments, which is negligible. The unique contribution of this research is to assist traditional universities to avail resources to fund the critical changes needed to combat COVID-19 and embrace the 4IR.